Suspended: Punishment, Violence, and the Failure of School Safety - Bell, Charles (Johns Hopkins University Press, 2021)
It will leave readers engrossed in the students' and parents' tearful narratives as they share how school suspension harmed students' grades, disrupted parents' employment, violated state and federal laws, and motivated families to withdraw from punitive districts.